The parametric optimization to enhance the pin-fin microchannel heatsink performance using splitter and water/silver nanofluid applying the two phase mixture model. (January 2023) - Wang, Dan; Hai, Tao
Abstract: The present study deals with the 3-D numerical analysis of hydrothermal characteristics of a pin-fin heatsink with splitter using two-phase mixture model. A parametric optimization was performed considering different Re numbers (500-2000) and nanoparticle concentrations (φ=0-1%) to determine the optimum operating conditions of the system yielding the highest heat transfer coefficient ( h ) and lowest pumping power ( W ˙ p ) . The outcomes showed that in the pin-fin heatsink with splitter, h (or W ˙ p ) increases by 2.8-7.8% (or 5.5%), 5.6-7.9%% (or 11.27%), and 5.9-6.6% (or 14.80%) for Re numbers of 1000, 1500, and 2000, respectively, over the other case without splitter. The enhancement in the h is obtained due to increasing the heat transfer surface area and better flow mixing that caused by using the splitters. The pressure drop, however, escalates due to increasing the contact surface area of the NF and the solid parts as well as mixing the vortexes formed around the pin-fins. In addition, mean CPU temperature for the case of splitter pin-fin heatsink is 0.52-0.79%, 0.45-0.65%, and 0.47-0.50% lower than that for the heatsink without splitter at Re numbers of 1000, 1500, and 2000, respectively. The figure of merit (FOM) was obtained as 1.06-1.16 indicating a better hydrothermal performance of the splitter heatsink as compared to the other case.